In situ synthesis, structural chemistry and vibrational spectroscopy of Zn-doped Ca5Mg4(VO4)6 - Anna S. Tolkacheva; Sergey N. Shkerin; Sofya A. Petrova; Olga M. Fedorova; Svetlana G. Titova; Ivan I. Leonidov (Chimica Techno Acta)
The phase formation of the solid solution Ca5Mg4–xZnx(VO4)6 (0≤x≤4) was studied in situ using differential scanning calorimetry and high-temperature X-Ray powder diffraction (XRPD). XRPD analysis shows the appearance of unavoidable secondary pyrovanadate phases using conventional synthesis methods. The local structure of the solid solution was verified by vibrational spectroscopy. The analysis of the infrared and Raman spectroscopy data allows establishing the main features between vanadate garnets and their isostructural analogs among natural silicates.